2015
DOI: 10.1186/s12889-016-2753-2
|View full text |Cite
|
Sign up to set email alerts
|

Why increasing availability of ART is not enough: a rapid, community-based study on how HIV-related stigma impacts engagement to care in rural South Africa

Abstract: BackgroundStigma is a known barrier to HIV testing and care. Because access to antiretroviral therapy reduces overt illness and mortality, some scholars theorized that HIV-related stigma would decrease as treatment availability increased. However, the association between ART accessibility and stigma has not been as straightforward as originally predicted.MethodsWe conducted a “situational analysis”—a rapid, community-based qualitative assessment to inform a combination HIV prevention program in high prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 63 publications
12
128
1
Order By: Relevance
“…The inevitability of one's death will be hovering at the back of one's mind, as the body gradually succumbs to the opportunistic infections as a result of the infection. This finding is in line with previous research, which shows that sometimes people cannot envisage a healthy identity when they are HIV positive, a situation which other researchers have labelled a "spoiled identity" (Aransiola, Imoyera, Olowookere & Zarowsky, 2014;Treves-Kagan, Steward, Ntswane, Haller, Gilvydis, Gulati, Barnhart & Lippman, 2016).…”
Section: Theme 2: Stigmasupporting
confidence: 82%
See 2 more Smart Citations
“…The inevitability of one's death will be hovering at the back of one's mind, as the body gradually succumbs to the opportunistic infections as a result of the infection. This finding is in line with previous research, which shows that sometimes people cannot envisage a healthy identity when they are HIV positive, a situation which other researchers have labelled a "spoiled identity" (Aransiola, Imoyera, Olowookere & Zarowsky, 2014;Treves-Kagan, Steward, Ntswane, Haller, Gilvydis, Gulati, Barnhart & Lippman, 2016).…”
Section: Theme 2: Stigmasupporting
confidence: 82%
“…From the participants' stories it emerged that VCT in Zimbabwe seems to be focused mainly on living positively with HIV and that disclosure appears to have been relegated to the background. It is true that a positive mind is essential in order to live longer with HIV, but HIV/AIDS status disclosure is also needed in order to curb the rate of HIV infections in Africa, where the rate is alarmingly high, since it is this silence that helps to fuel the spread of the epidemic (Aransiola et al, 2014;Tharao, Massaquoi & Teclom, 2006;Treves-Kagan et al, 2016).…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptability rates among ANC women in Africa are generally higher than those seen in previous years; 69% (35%-95%) (Cartoux M et al,1998). This could be attributed to increasing availability of ART and destigmatization of HIV infection (Treves-Kagan S et al,2016).…”
Section: Discussionmentioning
confidence: 60%
“…As of 2016, South Africa is initiating ART with all patients testing HIV positive regardless of CD4 count, in line with the recommendations by the World Health Organization (WHO) [12]. However, other studies have suggested that, on their own, biomedical interventions are not enough to deal with the epidemic [1821]. Structural and sociobehavioural factors have been considered major barriers to ART initiation [22,23].…”
Section: Introductionmentioning
confidence: 98%